2022
DOI: 10.1088/1742-6596/2314/1/012003
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Study on Biethanol Production from Starchy Foodwastes by Immobilized Saccharomyces cerevisiae

Abstract: Dumping of food wastes into the landfill resulted in major environmental pollution. However, attempted had been made to develop these wastes into a new renewable and sustainable energy. Liquid biofuels, bioethanol can be produced from a variety of feedstock including biomass and food crops or wastes. Therefore, in this study, starchy food wastes of bread, rice and potatoes were utilized as a potential feedstock for the bioethanol production. Yeast Saccharomyces cerevisiae was immobilized in 2% calcium alginate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
(25 reference statements)
3
2
0
Order By: Relevance
“…3. The ethanol concentration decreased with increasing pH and decreasing temperature, which is in agreement with previous study by Abdulla et al [13]. The maximum ethanol concentration of 0.2247 g/ml was achieved at 45℃ with pH 3.0.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…3. The ethanol concentration decreased with increasing pH and decreasing temperature, which is in agreement with previous study by Abdulla et al [13]. The maximum ethanol concentration of 0.2247 g/ml was achieved at 45℃ with pH 3.0.…”
Section: Resultssupporting
confidence: 92%
“…These two parameters were varied in the range of pH 3.0 -6.0, and 25 -45℃, while the incubation time was kept constant at 60 h. It was observed that pH and temperature have great effect on the ethanol concentration. This was further proven by the ANOVA which shows both pH and temperature have p-values <0.0001.The ethanol concentration decreased with increasing pH and decreasing temperature, which is in agreement with previous study by Abdulla et al[13]. The maximum ethanol concentration of 0.2247 g/ml was achieved at 45℃ with pH 3.0.…”
supporting
confidence: 91%
See 2 more Smart Citations
“…Degradation of hemicellulose gives rise to both glucose and other sugars such as xylose, arabinose, mannose, galactose, and rhamnose prior to fermentation, which converts the released sugars into bioethanol and CO 2 [6,20]. [21] tested the heating and acid treatment of papaya peel and only 0.8 g/L of bioethanol was produced. [22] tested acidic and alkaline conditions, followed by enzymatic hydrolysis with a cellulase complex to release free sugars from mango peel to produce bioethanol.…”
Section: Introductionmentioning
confidence: 99%